Consideration of strength development by three-dimensional visualization of porosity distribution in coal fly ash concrete. (March 2021) - Nakamura, Kengo; Inoue, Yuusuke; Komai, Takeshi
Abstract: Coal fly ash mixed with cement is a substitute civil engineering material that can secure the physical properties of concrete solidification. The benefits of this substitute were qualitatively evaluated the porosity distribution and phase change and the compressive strength resulting from chemical reactions. Visualization of the 3D porosity distribution of coal fly ash mixed material concrete with different material moisture ratios by X-ray CT is important for this purpose. The specimens were subjected to a uniaxial compression test and the porosity distribution was measured by X-ray CT after 7, 28, and 120 days. The strength at 120 days was 15–23 MPa for all specimens. Porosity increased 2% in all specimens as they aged. From the results of the 3D porosity distribution, specimens with a moisture ratio of 17 or 19 wt% had a porosity of 47% according to the porosity distribution histogram. These specimens also exhibited a porosity distribution with a layered structure. The other specimens (moisture ratio of 21 wt% with different mixing methods) were observed to have no layered structure and numerous large spherical pores. These results suggest that the porosity structure produced by the moisture ratio is important for the strength development of concrete containing coal fly ash. Moreover, a uniform porosity distribution and structure imparted by the correct moisture ratio appears to contribute to long-term strength development by effective chemical reactions in the specimen.